UTILIZATION OF DIGITAL APPLICATIONS AS AN EFFORT TO COLLECT APPROPRIATE FINANCIAL STATEMENTS WITH STANDARDS IN SMALL MICRO BUSINESS AND MEDIUM IN THE CITY OF DENPASAR - I Nyoman Sutapa; Ni Luh Putu Mita Miati; A.A. Pt. Agung Mirah Purnama Sari; Ni Putu Riski Martini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Micro, Small, and Medium Enterprises, hereinafter abbreviated as UMKM in Indonesia, are an important pillar of the economy in Indonesia. One of the principles of empowering UMKM is the realization of transparent, accountable, and fair public policies. However, there are still many UMKM that do not have financial records. Several researchers have researched the phenomenon of recording UMKM financial statements and researchers use these results to develop a research model by trying to explain the use of digital applications as a moderating variable. The purpose of this study was to examine the effect of financial management ability and accounting understanding on the preparation of financial statements according to standards. This study also examines the use of digital applications as a moderating variable. This research method uses the Partial Last square (PLS) model to test the effect of one variable on another with a population of 97,277 UMKM and a sample of 100 respondents is taken. The results of this study state that only the use of digital applications has a positive effect on the preparation of financial statements according to STANDARD AKUNTANSI KEUANGAN UMKM standards, while the digital application variable as a moderator cannot strengthen or weaken the interaction of the independent variables of financial management ability and accounting understanding.